Identifying multiple time scale rainfall controls on Mojave Desert ecohydrology using an integrated data and modeling approach for Larrea tridentata. Issue 6 (6th June 2015) - Ng, Gene‐Hua Crystal; Bedford, David R.; Miller, David M.
Abstract The perennial shrub Larrea tridentata is widely successful in North American warm deserts but is also susceptible to climatic perturbations. Understanding its response to rainfall variability requires consideration of multiple time scales. We examine intra‐annual to multiyear relationships using model simulations of soil moisture and vegetation growth over 50 years in the Mojave National Preserve in southeastern California (USA). Ecohydrological model parameters are conditioned on field and remote sensing data using an ensemble Kalman filter. Although no specific periodicities were detected in the rainfall record, simulated leaf‐area‐index exhibits multiyear dynamics that are driven by multiyear (∼3 years) rains, but with up to a 1 year delay in peak response. Within a multiyear period, Larrea tridentata is more sensitive to winter rains than summer. In the most active part of the root zone (above ∼80 cm), >1 year average soil moisture drives vegetation growth, but monthly average soil moisture is controlled by root uptake. Moisture inputs reach the lower part of the root zone (below ∼80 cm) infrequently, but once there they can persist over a year to help sustain plant growth. Parameter estimates highlight efficient plant physiological properties facilitating persistent growth and high soil hydraulic conductivity allowing deep soil moisture stores. We show that soil moisture as an ecological indicator is complicated by bidirectional interactions with vegetation that depend on time scale and depth. Under changing climate, Larrea tridentata will likely be relatively resilient to shorter‐term moisture variability but will exhibit higher sensitivity to shifts in seasonal to multiyear moisture inputs.